Intertumoral Heterogeneity of Primary Breast Tumors and Synchronous Axillary Lymph Node Metastases Reflected in IHC-Assessed Expression of Routine and Nonstandard Biomarkers - Kuncman, Wojciech; Orzechowska, Magdalena; Kuncman, Łukasz; Kordek, Radzisław; Taran, Katarzyna (Frontiers in Oncology, 2021)
Breast cancer (BC) remains a significant healthcare challenge. Routinely, the treatment strategy is determined by IHC-based assessment of the key proteins such as ER, PR, HER2, and Ki-67. However, it is estimated that over 75% of deaths result from metastatic tumors, indicating a need to develop more accurate protocols for intertumoral heterogeneity assessment and their consequences on prognosis. Therefore, the aim of this preliminary study was the identification of the expression profiles of routinely-used biomarkers (ER, PR, HER2, Ki-67) and additional relevant proteins (Bcl-2, cyclin D1, E-cadherin, Snail+Slug, GCDFP-15, PD-L1, and PRL-3) in primary breast tumors (PTs) and paired synchronous axillary lymph node (ALN) metastases. A total of 67 tissue samples met the inclusion criteria for the study. The expression status of biomarkers was assessed in PTs and ALN metastases using tissue microarrays followed by immunohistochemistry. In 11 cases, the shift of intrinsic molecular BC subtype was noticed between PTs and paired ALN metastases. Moreover, a significant disproportion in E-cadherin presence (p=0.0002) was noted in both foci, and the expression status of all proteins except for HER2 demonstrated considerable variance (k=1, p<0.0.0001). Importantly, in around 30% of cases, the ALN metastases demonstrated discordance, i.e. loss/gain of expression, compared to the PTs. Intertumoral synchronous heterogeneity in both foci (primary tumor and node metastasis) is an essential phenomenon affecting the clinical subtype and characteristics of BC. Furthermore, a greater understanding of this event could potentially improve therapeutic efficacy.